Real-time PCR을 이용한 스트레스에 따른 벼의 Receptor Like Kinase (RLK) 유전자의 발현 변화 분석 - 강민희(Min Hee Kang); 김일욱(Il Wook Kim); 한상훈(Sang Hoon Han); 윤충효(Choong Hyo Yun); 윤병수(Byoung Su Yoon) (Journal of plant biotechnology, 2008)
In plant, Receptor-like kinases (RLKs) are protein family, though its function is not yet understood, consisted of a predicted signal sequence, single transmembrane region, and cytoplasmic kinase domain. RLKs are involved in hormonal response pathways, cell differentiation, plant growth and development, self-incompatibility, and symbiont and pathogen recognition. In this study, expression levels of RLG1, RLG5, RLG6, RLG#6, RLG8, RLG10, RLG17, RLG18 and RLG20 were analyzed by Real-time PCR, when rice (Oryzae sativa) was treated abiotic stress. The expression levels of all RLGs were compared each other by analyzed value of threshold cycles ($C_T$). Consequently, RLGs were suppressed by NaCl as salinity stress, and expression of each RLK genes were showed difference treated salicylic acid and wound, respectively. However, All RLGs were induced under low temperature condition. Therefore, our results indicate protection-function of RLK genes to be an early response of rice against cold weather. 식물의 Receptor like kinase (RLK) 단백질들은, 그 기능이 잘 알려져 있지 않지만, signal sequence, single transmembrane region, cytoplasmic kinase 도메인으로 구성되어 있다 RLK gene (RLGs)는 호르몬 반응 경로, 세포 분열, 식물의 성장과 발달, 자가 불수분 그리고 공생과 병원균 인식과 연관되어 있다고 보고되었다. 본 연구에서는 벼의 RLGs 중 RLG1, RLC5, RLG6, RLG#6, RLG8, RLG10, RLG17, RLG18, RLG20의 스트레스에 따른 발현 변화를 real-time PCR을 사용하여 분석하여 분자적 특징을 확인하였다. Threshold cycle ($C_T$) 수치의 변화를 통해 발현 변화를 비교하여 결과적으로, NaCl에 대해서는 모두 감소하는 경향을 확인하였으며, Salicylic acid와 상처에 대해서는 각 RLGs에 따라 발현 변화가 다르게 나타났다. 이에 비교하여 저온에서는 모든 RLGs발현이 증가하였다. 따라서 본 연구에서는 냉해에 의한 벼의 생산성 감소를 벼의 RLK에서 확인된 분자적 특징을 이용함으로써 신 기능성 품종의 개발을 통해 극복 할 수 있을 것이라는 가능성을 보여주었다.